The role of R&D-intensive clusters for regional competitiveness - Reinhold Kosfeld; Timo Mitze (Philipps-University Marburg, School of Business and Economics, 2020)
Modern cluster theory provides reasons for positive external effects that accrue from the interaction of spatially proximate firms operating in common and related fields of economic activity. In this paper, we examine the impact of R&D-intensive clusters as a key factor of regional competitiveness on productivity and innovation growth. In analogy to the industry-oriented concepts of related and unrelated variety (Frenken, Van Oort, Verburg 2007), we differentiate between effects of cluster specialisation and diversity. The identification of R&D-intensive clusters is based on a hybrid approach of qualitative input-output analysis and spatial scanning (Kosfeld and Titze 2017). Our empirical study is conducted for a panel of German NUTS-3 regions in 2001-2011. To comprehensive account for specialisation and diversity effects of clustering we adopt a spatial econometric approach, which allows us to identify these effects beyond the geographical boundaries of a single region. After controlling for regional characteristics and unobserved heterogeneity, a robust "cluster strength" effect (i.e. specialization) on productivity growth is found within the context of conditional convergence across German regions. With regard to the underlying mechanisms, we find that the presence of a limited number of R&D-intensive clusters in specific technological fields is most strongly linked to higher levels of regional productivity growth. While we also observe a positive effect of cluster strength on innovation growth once we account for spatial spillovers, no significant effects of "cluster diversity" can be identified. This indicates that some but not all cluster-based regional development strategies are promising policy tools to foster regional growth processes.
Keywords: L16; R11; R15; 330; industry clusters; regional competitiveness; cluster specialisation; cluster diversity; correlated random effects model